2014
DOI: 10.7860/jcdr/2014/8602.4909
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative and Quantitative Analysis of AgNORs in Keratocystic Odontogenic Tumor, Unicystic Ameloblastoma and Multicystic Ameloblastoma

Abstract: This concludes the expediency of AgNOR staining in reflecting the high proliferation rate and a more aggressive behavior of KCOT in comparison to MA and UA which signifies requirement of a more hostile surgical approach in KCOT to avoid recurrences following different treatment modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Our study showed highest index of AgNORs and Ki-67 in OKC compared to DC and UA. Similar findings were reported in previous studies (Ananthaneni et al, 2014;A. Gadbail et al, 2012;A.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study showed highest index of AgNORs and Ki-67 in OKC compared to DC and UA. Similar findings were reported in previous studies (Ananthaneni et al, 2014;A. Gadbail et al, 2012;A.…”
Section: Discussionsupporting
confidence: 93%
“…DC is less aggressive and deserves special attention because of its possible transformation into ameloblastoma (Bhushan, Rao, Navata, & Kumar, 2014). The AgNOR's and Ki-67 counting have been useful for evaluating the aggressive behavior of OKC, DC, and UA (Ananthaneni, Udayashankar, Guduru, & Ramprasad, 2014;Jaafari-ashkavandi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative analysis showed small to large oval AgNOR's in keratocystic odontogenic tumor and few clusters in multicystic ameloblastoma whereas in unicystic ameloblastoma irregular clusters were seen and the results are correlating with present study. 12 Navjeevraj et al, (2016) and Alessandra Dutra da Silva et al, (2016) assessed and compared the role of AgNORs in cell proliferation between ameloblastic carcinoma, solid and cystic variants of ameloblastoma. They found higher mean AgNOR in ameloblastic carcinoma than in solid ameloblastoma and unicystic ameloblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] The impaired nuclear activity in proliferating cells results in a higher AgNOR count, which relates to the lesion's malignant potential. [ 23 ] Quantification of interphase AgNORs is useful in the assessment of cell kinetics. [ 24 ] Determination of ploidy, proliferation activity, and metabolic cell activity not associated with proliferation by AgNOR count has been described as a good method.…”
Section: Discussionmentioning
confidence: 99%